Hydrogels for the treatment of rheumatoid arthritis - Yi, Jiafeng; Liu, Yubo; Xie, Hongbin; An, Haoming; Li, Chao; Wang, Xing; Chai, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract: Rheumatoid Arthritis (RA) is a universal disease that severely affects the normal function of human joints and the quality of life. Millions of people around the world are diagnosed with rheumatoid arthritis every year, carrying a substantial burden for both the individual and society. Hydrogel is a polymer material with good mechanical properties and biocompatibility, which shows great potential in the treatment of RA. With the progress of tissue engineering and biomedical material technology in recent years, more and more studies focus on the application of hydrogels in RA. We reviewed the progress of hydrogels applied in rheumatoid arthritis in recent years. Also, the needed comprehensive performance and current applications of therapeutic hydrogels based on the complex pathophysiological characteristics of rheumatoid arthritis are also concluded. Additionally, we proposed the challenges and difficulties in the application of hydrogels in rheumatoid arthritis and put forward some prospects for the future research.